Knowledge and self efficacy associated to HIV and AIDS prevention in Chilean women - Villegas Rodriguez, Natalia Andrea; Ferrer Lagunas, Lilian Marcela; Cianelli Acosta, Rosina; Miner, Sarah Mary; Lara Campos, Loreto Andrea; Peragallo, Nilda (Investigación y Educación en Enfermería, 2011)
Objective. To assess the relationship between knowledge and self efficacy associated to HIV/AIDS in women from Chile with social disadvantages. Methodology. Correlation study that uses the baseline assessment of the “Testing an HIV and AIDS intervention in Chilean women” study, carried out between 2006 and 2008, with a sample of 496 women between 18 and 49 years old, in 2 neighborhoods of Santiago de Chile. Participants answered a structured survey conducted by trained interviewers. The survey included questions about sociodemographic information, risk behaviors and a self-efficacy knowledge scale among others. Results. The average age was 32.3+9.1 years, 72.2% live with their partner and 42.7% have completed high school education. The mean score of HIV infection knowledge was 8.9+2.5, while the mean score for the three scales used to measure self-efficacy were: “Peer rules” =9.8+3.6, “Risk reduction intentions =12.2+3.6 and “Self Efficacy Form”=20.2+4.7. HIV knowledge had a weak positive correlation with the “Risk reduction intentions” scale (r=0.19; p< 0.0001) and the “Self Efficacy Form” scale (r=0.34; p< 0.0001), however there was no correlation with the “Safe sex peer rules” (r=0.13;p=0.78). Conclusion. There is a weak positive correlation between the HIV/AIDS related knowledge and self-efficacy among Chilean with social disadvantages.